ANALISIS PEMBATALAN PERJANJIAN PENGIKATAN JUAL BELI (PPJB) SECARA SEPIHAK YANG DILAKUKAN OLEH KREDITUR (STUDI PUTUSAN PENGADILAN NEGERI BEKASI NOMOR 39/PDT.G/2019/PN.BEKASI) - Vanny Grace Angelina Tampubolon; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2021)
Buying The Buying and Selling Binding Agreement has contained the rights and obligations of the parties who make it. Buying and Selling Binding Agreements (PPJB) often experience obstacles in practice, problems related to the agreement resulted in the agreement being canceled. The Buying and Selling Binding Agreement (PPJB) may be cancelled unilaterally by either party or by agreement of both parties. Unilateral cancellation of the agreement, of course, causes losses for the parties, so there needs to be a protection due to the cancellation of the agreement. This writing has a problem, namely how the mechanism and legal consequences for the cancellation of PPJB in the Decision of the Bekasi District Court Number 39 / Pdt.G / 2019 / PN. Bekasi. This writing also aims to find out the mechanism and legal consequences of the cancellation of PPJB in the Decision of the Bekasi District Court No. 39 / Pdt.G / 2019 / PN. Bekasi. This research uses this type of normative or doctrinal juridical law research. The short method used is a statute approach by collecting data that includes library research based on qualitative data analysis that can be interpreted in the form of sentences described systematically, clearly, and in detail. The conclusion of this study is the void of norms related to the creation of the Unilateral Buying and Selling Binding Agreement (PPJB), so as to cause legal consequences and agreements that have previously been made to become void or in other words the agreement becomes terminated and the parties are no longer bound as long as necessary as stipulated in Article 1266 of the Civil Code. As a result of the cancellation, the debtor feels aggrieved and the creditor must return the down payment (DP) that has been paid by the debtor to the creditor in accordance with the Decision of the Bekasi District Court No. 39 / Pdt.G / 2019 / PN. Bekasi). If the Creditor does not carry out in accordance with the Court's Decision, then there are sanctions that must be accepted.